An Investigation into Green Attitude and Behavior of Consumers as a Step towards Eco-Friendly Environment: Exploring the Impact of Green Attitude on Consumer Behavior towards Eco-friendly Products (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The association amongst decisiveness, accomplishment, and the boldness of buyers to go for green products is undoubted. The vendors crave to categorize the characteristics that boost the consumer to acquire green merchandise as green marketing is multifarious from publicizing in the conformist system. Green marketing has advanced as an utmost imperative range of awareness for marketers as it delivers practicable reparations copious plentiful of the corporations in India are in the fruition of promotion as eco-friendly formations attributable to substantiated government sustenance and reformation in the penchant of the customers universally. Nevertheless, insufficient research as regards green marketing has been buoyed in India. A demand based on consumer’s awareness regarding the environment is attracting the consumers towards green products is acquiring prominence.